A Practical Approach to the Diagnosis and Management of Hair Loss in Children and Adolescents - Xu, Liwen; Liu, Kevin X.; Senna, Maryanne M. (Frontiers in Medicine, 2017)
Hair loss or alopecia is a common and distressing clinical complaint in the primary care setting and can arise from heterogeneous etiologies. In the pediatric population, hair loss often presents with patterns that are different from that of their adult counterparts. Given the psychosocial complications that may arise from pediatric alopecia, prompt diagnosis and management is particularly important. Common causes of alopecia in children and adolescents include alopecia areata, tinea capitis, androgenetic alopecia, traction alopecia, trichotillomania, hair cycle disturbances, and congenital alopecia conditions. Diagnostic tools for hair loss in children include a detailed history, physical examination with a focused evaluation of the child’s hair and scalp, fungal screens, hair pull and tug test, and if possible, light microscopy and/or trichoscopy. Management of alopecia requires a holistic approach including psychosocial support because treatments are only available for some hair loss conditions, and even the available treatments are not always effective. This review outlines the clinical presentations, presents a diagnostic algorithm, and discusses management of these various hair loss disorders.